PENINGKATAN KESADARAN LINGKUNGAN DENGAN PELATIHAN PENGOLAHAN SAMPAH DI DESA SUMBERMULYO KECAMATAN BAMBANGLIPURO - Mulasari, Surahma Asti; Bayu, Mohammad; Inaz, Aulya (Universitas Ahmad Dahlan, Yogyakarta, 2020)
Bambanglipuro sub-district is a sub-district in the lowlands. The Capital District is 22 meters above sea level. Distance of the Capital District to the Government Center (Capital) of Bantul Regency is 10 Km. Bambanglipuro sub-district has a climate like a low-lying area in the tropics with hot weather as its trademark. The highest temperature recorded in Bambanglipuro sub-district is 31ÂºC with the lowest temperature of 23ÂºC. The area stretch in Bambanglipuro sub-district is 99.5% in the form of flat to choppy areas and 0.5% in the form of choppy to hilly areas. The purpose of this service was to create a community of Sumbermulyo Village, Bambanglipuro sub-district who is independent, especially in terms of waste management and to improve the economy of Sumbermulyo Village, Bambanglipuro sub-district through the results of waste management in the environment. The method used in this service is through counseling and training on waste management located in Sumbermulyo Village, Bambanglipuro sub-district in February 2020 with a predetermined date. Community service has been carried out well and smoothly. Sumbermulyo Village Community Bambanglipuro sub-district shows a positive response and plays an active role in all the activities carried out. The community wants that there is further guidance, especially in the field of waste management so that community empowerment can run optimally Â